Immunotherapy-Induced Acute Gastritis: First Case Report of Nivolumab Re-Challenge after Severe Immune-Mediated Inflammatory Response - Raphael, Ari; Menachem, Yoram; Barazovski, Eli; Shibolet, Oren; Geva, Ravit (Archives of Clinical and Medical Case Reports, 2022)
Background: The use of Checkpoint Inhibitors (CPIs) exposes patients to CPI immune-related adverse events (irAEs) that affect a variety of body organs and systems. IrAEs of the upper gastrointestinal tract and gastritis are rare manifestations of CPI-related IrAEs, with only a few cases reported in the literature. Currently, there are no guidelines for the evaluation, treatment and re-challenge after CPI-mediated gastritis. Case Presentation: A fifty-eight-year-old male patient with hepatocellular carcinoma developed a rare irAE of acute gastritis after treatment with nivolumab. The immunotherapy was withdrawn and corticosteroids were administered, leading to complete symptom resolution. Nivolumab was then reinstated with good anti-tumor response and without recurrence of gastritis. Conclusion: In our experience, nivolumab re-challenge after immune related gastritis was safe and resulted in a continued good clinical response.